Plant Stimuli and Their Impact on Brown Marmorated Stink Bug Dispersal and Host Selection - Blaauw, Brett R.; Hamilton, George; Rodriguez-Saona, Cesar; Nielsen, Anne L. (Frontiers in Ecology and Evolution, 2019)
A diverse diet in polyphagous insects satisfies changing nutritional needs but the choice of host plant may vary throughout the insect and plant life cycle. The behaviors associated with host choice in the immature stages may differ from the egg laying site chosen by the mother. To evaluate this for an important agricultural pest, we looked at host choice over two growing seasons for the invasive Halyomorpha halys. H. halys has a host breadth of over 170 known species in its invaded range and adults can satisfy nutritional needs through a strong dispersal capacity. Nymphs are more limited in their ability to choose host plants and we investigated if they make a choice that differs from the source plant (to simulate maternal choice) and characterized volatile organic compounds that are present during attraction. In a mark-release-recapture experiment we quantified dispersal and host choice by nymphs to four common vegetable hosts throughout the growing season. Applying an attraction index to quantify host choice we identified that nymphs switch host plants depending on host phenology. Plants with maturing fruits were most attractive. Volatile organic compounds were collected from host plants during the same time period. Principal component analysis categorized phenol, undecane, decanal, caryophyllene, and nonanal as compounds associated with host plants during peak attractive periods. Thus, the availability of suitable food and associated olfactory cues appears to be influencing the spatiotemporal distribution of H. halys within the agroecosystem. Exploiting dispersal behavior and olfactory cues may be used to help increase the effectiveness and efficiency of current management practices for this severe and widespread pest.